2018
DOI: 10.1128/aem.02797-17
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Exposure-Sedum alfredii Planting Interactions Shape the Bacterial Community in the Hyperaccumulator Plant Rhizosphere

Abstract: Rhizospheric bacteria play important roles in plant tolerance and activation of heavy metals. Understanding the bacterial rhizobiome of hyperaccumulators may contribute to the development of optimized phytoextraction for metal-polluted soils. We used 16S rRNA gene amplicon sequencing to investigate the rhizospheric bacterial communities of the cadmium (Cd) hyperaccumulating ecotype (HE) in comparison to its nonhyperaccumulating ecotype (NHE). Both planting of two ecotypes of and elevated Cd levels significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…In fact, all the treatments apart from P8 and P9 showed a significantly lower richness value compared to their correspondent unplanted control. This result, in agreement with previous studies, 50 seems to reflect a prolonged selective pressure exerted by the plants on the bacterial populations in the rhizosphere, which was of course absent in the nonplanted controls. Taken together, the analyzed α-diversity indices indicated that the microbial communities associated with P1 ( P. arundinacea ) and P3 ( F. arundinacea ) were the most impacted by the applied treatment and showed the higher number of significantly different indices compared to the related unplanted control (C2).…”
Section: Resultssupporting
confidence: 93%
“…In fact, all the treatments apart from P8 and P9 showed a significantly lower richness value compared to their correspondent unplanted control. This result, in agreement with previous studies, 50 seems to reflect a prolonged selective pressure exerted by the plants on the bacterial populations in the rhizosphere, which was of course absent in the nonplanted controls. Taken together, the analyzed α-diversity indices indicated that the microbial communities associated with P1 ( P. arundinacea ) and P3 ( F. arundinacea ) were the most impacted by the applied treatment and showed the higher number of significantly different indices compared to the related unplanted control (C2).…”
Section: Resultssupporting
confidence: 93%
“…For example, the inoculation of Pseudomonas aeruginosa and Burkholderia gladioli enhanced Cd tolerance in the seedlings of Lycopersicon esculentum ( Khanna et al, 2019 ). Moreover, many reports have shown that bacterial-community structure and diversity respond to direct heavy-metal contamination in soil ( Abdu, Abdullahi & Abdulkadir, 2017 ; Luo et al, 2018 ; Hou et al, 2018 ). For example, the bacterial community of soils contaminated with Pb, Zn, and Cr significantly differ, with Zn decreasing both diversity and species richness at the species and family levels, while plant-species richness was not correlated with bacterial diversity ( Golebiewski et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [48] also suggested heavy metal contamination could play a more important role in shaping bacterial diversity. The bacterial growth rate and biomass in soils was found to consistently diminish along the Cd gradient, regardless of planting Sedum alfredii [49]. Similarly, Golebiewski et al [50] found that species richness, diversity, and bacterial communities in soils with low levels of Pb contamination were higher than in highly polluted soils.…”
Section: Effects Of S Integra Planting and Pb Pollution On Soil Propmentioning
confidence: 92%